Gambaran Pengetahuan dan Praktik Pemenuhan Gizi Seimbang pada Remaja Perempuan - Amara Putri Hermawanti; Mira Trisyani Koeryaman; Lilis Mamuroh (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescents are a vulnerable age group prone to nutritional problems due to changes in dietary patterns, which often result in an imbalance between nutritional needs and daily intake. In addition to increasing the risk of obesity and anemia among adolescent girls, this imbalance also contributes to the risk of stunting in future generations. This study aims to determine the knowledge and practices regarding balanced nutrition among adolescent girls at SMKS Mutiara Bangsa Purwakarta. The research method used was quantitative descriptive with a total sampling technique involving 106 female students from grades 10 to 12. Data collection was conducted using a questionnaire consisting of 44 items to explore knowledge and practices regarding balanced nutrition. The data were analyzed univariately and presented in the form of frequency distributions and descriptive statistics. The results showed that the majority of respondents had a level of knowledge regarding balanced nutrition in the “inadequate” category (32 respondents, 30.2%), followed by the “good” category (74 respondents, 69.8%). Regarding the practice of balanced nutrition, the majority of respondents were in the “inadequate” category (57 respondents, 46.2%), while 49 respondents (53.8%) were in the “good” category. Based on the research results, this indicates that adolescents’ level of nutritional knowledge has not been fully implemented in daily nutritional practices. Therefore, efforts to raise awareness and change nutritional behaviors starting in adolescence are needed to support optimal growth, improve health status, and prevent various nutritional problems in the future. Keywords: Adolescents, Nutritional Knowledge and Practices, Nutritional Status. ABSTRAK Remaja adalah kelompok usia rentan mengalami masalah gizi akibat perubahan pola makan yang seringkali ditemukan ketidakseimbangan antara kebutuhan dan pemenuhan gizi harian. Selain menimbulkan potensi obesitas dan anemia pada remaja perempuan, juga sebagai salah satu kontrubutor risiko stunting pada generasi berikutnya di masa mendatang. Penelitian ini bertujuan untuk mengetahui bagaimana pengetahuan dan parktik pemenuhan gizi seimbang pada remaja perempuan di SMKS Mutiara Bangsa Purwakarta. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan teknik total sampling pada 106 siswi dari kelas 10 sampai 12. Pengumpulan data dilakukan menggunakan kuesioner sebanyak 44 item pertanyaan untuk menggali pengetahuan dan praktik pemenuhan gizi seimbang. Data dianalisis secara univariat dan disajikan dalam bentuk distribusi frekuensi dan statistik deskriptif. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki tingkat pengetahuan gizi seimbang dalam kategori kurang yaitu 32 (30,2%), diikuti kategori baik 74 (69,8%). Sedangkan pada praktik pemenuhan gizi seimbang, sebagian besar responden berada pada kategori kategori kurang 57 (46,2%), dan kategori baik 49 (53,8%). Berdasarkan hasil penelitian, ini menunjukkan bahwa tingkat pengetahuan remaja tentang gizi belum sepenuhnya diimplementasikan dalam praktik pemenuhan gizi sehari-hari. Oleh karena itu, diperlukan upaya peningkatan kesadaran dan perubahan perilaku gizi sejak usia remaja guna mendukung pertumbuhan optimal, meningkatkan status kesehatan, serta mencegah terjadinya berbagai masalah gizi di masa mendatang. Kata Kunci: Pengetahuan Gizi, Praktik Gizi, Remaja, Status Gizi, Kesehatan Remaja.